Short open reading frame genes in innate immunity: from discovery to characterization. Issue 9 (September 2022) - Malekos, Eric; Carpenter, Susan
Abstract : Next-generation sequencing (NGS) technologies have greatly expanded the size of the known transcriptome. Many newly discovered transcripts are classified as long noncoding RNAs (lncRNAs) which are assumed to affect phenotype through sequence and structure and not via translated protein products despite the vast majority of them harboring short open reading frames (sORFs). Recent advances have demonstrated that the noncoding designation is incorrect in many cases and that sORF-encoded peptides (SEPs) translated from these transcripts are important contributors to diverse biological processes. Interest in SEPs is at an early stage and there is evidence for the existence of thousands of SEPs that are yet unstudied. We hope to pique interest in investigating this unexplored proteome by providing a discussion of SEP characterization generally and describing specific discoveries in innate immunity. Abstract : Significance: Coding from noncoding: in this review we explore the emerging roles of bifunctional genes in contributing to the innate immune response. Highlights: New approaches have implicated hundreds of long noncoding RNAs as potential protein coding genes through overlooked short open reading frames (sORFs). There are many thousands of sORFs, with multiple lines of evidence supporting production of sORF-encoded peptides (SEPs), compiled in databases but uninvestigated. Confirmation of production and functional characterization can be nuanced, but thoughtful interrogation has already expanded the known proteome and our understanding of important biological pathways. This includes contributions to innate immune function in mouse and human. Although the expanding proteome is likely to interest investigators from all fields, there is reason to believe that immunologists are particularly well positioned to make impactful discoveries.